PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU SMK (SEKOLAH MENENGAH KEJURUAN) DI KECAMATAN CURAHDAMI, BONDOWOSO - Nurma Yunita; Supardi Supardi; Muhaimin Dimyati (STIE Mandala Jember, 2022)
This research aim to examine principal’s role as an educator, supervisor and motivator. Based on problem identification, the researcher will research about principal’s role in improving teacher’s professionalism in SMK Curahdami. Empower teacher’s competencies, conduct training, special coaching program such as sertifikasi. In this case, sertifikasi can be used as teacher’s skill measurement to be a professional teacher. The existence of this program will spur the spirit of teachers to improve themselves, improve the quality of knowledge, and professionalism in education. Improving teacher’s knowledge by delegating teacher in education activities such as workshop, improving teacher’s creativity by motivate and support them in increasing their teaching ability. Keywords: educator, supervisor, motivator